Macromastia Surgery: a Proven Approach Perfected Over 25 Years in Plastic Aesthetic Surgery - Eugen Gabriel TURCU (Modern Medicine)
Macromastia is a rare condition in women and is characterized by an abnormal growth of the mammary glands. Macromastia is considered breast hypertrophy in which the excess of breast glandular tissue exceeds 3% of the total body weight1. In specialized literature, the term gigantomastia is also used7. Some authors consider the term macromastia synonymous with gigantomastia, especially since the repercussions on the general state of the body are the same. Other authors consider that the two terms, macromastia or gynecomastia, are not synonymous7. Currently, there is no unanimous agreement on the definition of the two terms. The article presents my experience of 25 years in the surgical management of macromastia (gigantomastia) on a number of 364 cases. The surgical solution was based on the use of the modified McKissock technique (if the breast resection involved the excision of up to 1.5 kg of mammary gland from the level of a single breast) or the breast reduction with a free areola graft in the Pitanguy technique (if the resection involved more than 1.5 kg and the positioning of the new areola exceeds 15 cm from the level of the submammary groove. The clinical evaluation is very important for establishing the surgical management. The benefits of breast reduction in these cases are evident immediately postoperatively.